2021
DOI: 10.3389/fphar.2020.617149
|View full text |Cite
|
Sign up to set email alerts
|

Triumeq Increases Excitability of Pyramidal Neurons in the Medial Prefrontal Cortex by Facilitating Voltage-Gated Ca2+ Channel Function

Abstract: Combination antiretroviral therapy (cART) suppresses HIV-1 replication, improves immune function, and prolongs the life of people living with HIV (PLWH). However, cART also induces neurotoxicity that could complicate HIV-induced neurodegeneration while reduce its therapeutic efficacy in treating HIV/AIDS. Triumeq is a first-line cART regimen, which is co-formulated by three antiretroviral drugs (ARVs), lamivudine (3TC), abcavir (ABC), and dolutegravir (DTG). Little is known about potential side effects of ARVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Consistent with this observation, we found a trend towards reduced medial orbitofrontal cortex in all groups, although the differences were only statistically significant in individuals who began cART later. While INSTI have been reported to induce neurotoxicity through several molecular mechanisms in in vitro studies, such as altering lysosomal function leading to neuroinflammation 41 or hyperexcitability of medial prefrontal cortex pyramidal neurons 42 , our data show that the longer-term effect of HIV-1 itself in the brain could be more harmful than potential INSTI-related neurotoxicity, at least to the extent that neuroimaging can reveal clinically significant findings.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with this observation, we found a trend towards reduced medial orbitofrontal cortex in all groups, although the differences were only statistically significant in individuals who began cART later. While INSTI have been reported to induce neurotoxicity through several molecular mechanisms in in vitro studies, such as altering lysosomal function leading to neuroinflammation 41 or hyperexcitability of medial prefrontal cortex pyramidal neurons 42 , our data show that the longer-term effect of HIV-1 itself in the brain could be more harmful than potential INSTI-related neurotoxicity, at least to the extent that neuroimaging can reveal clinically significant findings.…”
Section: Discussionmentioning
confidence: 54%
“…We found that co-application of Nim protected only against BIC-induced synapse loss, and this protection was incomplete. The finding that BIC-induced synapse loss has a VGCC component is interesting as the cART regimen Triumeq (DTG/ABC/3 TC) has been found to increase prefrontal pyramidal neuron excitability through low voltage activated L-type VGCCs, suggesting that as a class ISTIs might activate Ca 2+ channels ( Chen et al, 2020 ). Additionally, we assessed whether excessive glutamatergic signaling contributed to ARV-induced synapse loss as PIs have been shown to disrupt astrocytic excitatory amino acid transporter 2 expression and would thus elevate extracellular glutamate concentrations ( Vivithanaporn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that neuroHIV stems, at least partially, from disruption of this communication, impairing neurotransmission, synapse formation/dissolution and neuroimmune communication. Some studies suggest that antiretroviral (ARV) drugs themselves may contribute to these changes in neuroimmune communication and neurological dysfunction (19)(20)(21)(22). The data from Tripathi et al support this possibility, showing that in both isolated rodent microglia and in HIV-1 transgenic rats, exposure to ART mediates microglial activation through oxidative stress-mediated lysosomal dysfunction.…”
Section: Advances In Understanding Neurohiv Associated Changes In Neuroimmune Communication In the Combined Anti-retroviral Therapy (Cartmentioning
confidence: 99%